17
$\begingroup$

How can I prove the following conjectured identity? $$\int_0^\pi\frac{\ln(2+\cos\phi)}{\sqrt{2+\cos\phi}}d\phi\stackrel?=\frac{\ln3}{\sqrt3}K\left(\sqrt{\frac23}\right),\tag1$$ where $K(x)$ is the complete elliptic integral of the 1ˢᵗ kind: $$K(x)={_2F_1}\left(\frac12,\frac12;\ 1;\ x^2\right)\cdot\frac\pi2.\tag2$$

$\endgroup$
  • $\begingroup$ $$I(n)=\int_0^\pi(2+\cos\phi)^nd\phi\quad\iff\quad\int_0^\pi\dfrac{\ln(2+\cos x)}{\sqrt{2+\cos x}}dx=I'\Big(-\tfrac12\Big)$$ $\endgroup$ – Lucian Feb 27 '14 at 8:06
  • $\begingroup$ With Mathematica I got $\mbox{LHS} - \mbox{RHS} = -0.169648$ $\endgroup$ – Felix Marin Mar 7 '14 at 23:12
  • $\begingroup$ @FelixMarin You should use EllipticK[x^2] to represent $K(x)$ in Mathematica. See the MathWorld link in my question. $\endgroup$ – Vladimir Reshetnikov Mar 8 '14 at 0:36
  • $\begingroup$ @VladimirReshetnikov $0$ k. I just checked it: $-9.15712 \times 10^{-13}$. $\endgroup$ – Felix Marin Mar 8 '14 at 4:41
  • $\begingroup$ @Felix Marin that's small enough of a margin of error to be caused by numerical instability/rounding errors $\endgroup$ – frogeyedpeas Jul 19 '14 at 4:25
20
+50
$\begingroup$

$\int^{\pi}_0\cos^{2k+1}\phi d\phi=0$, and $$\int^{\pi}_0\cos^{2k}\phi d\phi=\sqrt{\pi}\Gamma(k+1/2)/\Gamma(k+1)=2^{-2k}\pi\binom{2k}{k}.$$

Therefore $$ \begin{align*} I(n) &=\int^{\pi}_0\sum_{m=0}^{\infty}2^{n-m}\binom{n}{m}\cos^m\phi~d\phi\\ &=2^n\sum_{m=0}^{\infty}2^{-m}\binom{n}{m}\int^{\pi}_0\cos^m\phi~d\phi\\ &=2^n\pi\sum_{k=0}^{\infty}2^{-2k}\binom{n}{2k}2^{-2k}\binom{2k}{k}\\ &=2^n\pi~{}_2F_1\left(\frac{1-n}2,-\frac{n}{2};1;\frac14 \right)\\ &=2^n\pi\left(\frac23\right)^{-n}~{}_2F_1\left(-n,\frac{1}{2};1;\frac23\right)\\ &=3^n\pi~{}_2F_1\left(-n,\frac{1}{2};1;\frac23\right)\\ \end{align*} $$ Using DLMF 15.8.13 with $a=-n$, $b=1/2$ and $z=2/3$.

We note that $I(-1/2)=\frac{2}{\sqrt{3}}K(\sqrt{2/3})$.

Edit: We have $$ I(n)=3^n\pi~{}_2F_1\left(-n,\frac{1}{2};1;\frac23\right)=\frac{\pi}{\sqrt{3}}~{}_2F_1\left(n+1,\frac{1}{2};1;\frac23\right)=3^{n+1/2}I(-n-1).$$

Therefore, If we write $J(n)=3^{-n/2}I(n)$, then $J(n)=J(-n-1)$, and consequently $J'(-1/2)=0$.

Thus $$ \begin{align*} I'(-1/2) &=\left.\frac{d}{dn}3^{n/2}J(n)\right|_{n=-1/2}\\ &=\left.\left(3^{n/2}J'(n)+3^{n/2}\frac{\log 3}{2}J(n)\right)\right|_{n=-1/2}\\ &=3^{-1/4}\frac{\log 3}{2}J(-1/2)\\ &=\frac{\log 3}{2}I(-1/2)\\ &=\frac{\log 3}{\sqrt{3}}K(\sqrt{2/3}). \end{align*} $$

$\endgroup$
  • 1
    $\begingroup$ Here are some formulas. $\endgroup$ – Lucian Mar 1 '14 at 14:50
  • $\begingroup$ very nice solution +1 $\endgroup$ – Shobhit Bhatnagar Mar 2 '14 at 7:30

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.